Nigeria : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Nigeria's 2002 Article IV Consultation highlights that major macroeconomic imbalances had emerged as a result of sharp increases in government spending and expressed concern at the risks of a further acceleration of inflation and continuing instability in the exchange market. The overall fiscal balance deteriorated sharply in 2001, the external accounts worsened, and inflation accelerated. The overall stance of fiscal policy remains highly expansionary in 2002, notwithstanding efforts by the authorities to contain capital spending. Lax financial policies have led to a sharp fall in international reserves.